Strong Terahertz radiation generation via wakefield in collisional plasma - Hitendra K. Malik; Divya Singh; Ravinder Kumar (Journal of Taibah University for Science, 2020)
The present calculations show that the application of an external magnetic field can generate additional component of the wakefield suitable for Terahertz (THz) radiation generation in a collisional plasma. Based on the approach of perturbation technique under quasi-static approximation, a study is made on the field of emitted radiation pulses from the wakefield when the super-Gaussian laser beams are used. The field of the radiation becomes stronger when stronger magnetic field is applied and the same is the case for the lasers of higher index.